Conceptualization of the social support and the social support network - Aranda B., Carolina (2013)
Many are the concepts and approaches whose have been proposed in the study of the social support as social support networks, as well as the use of some of these concepts to relate either social support or social support networks to the conditions and its importance in the protective role of it. The route on the conceptualization of both variables occurs since the fifties to the most current, closing with some brief conclusions.